Exploring the Impact of Tinkercad-Assisted Learning on Student Performance in Industrial Electronics Subject - Asbendri BL; Sartika Anori; Ika Parma Dewi; Efrizon (Journal of Hypermedia & Technology-Enhanced Learning, 2024)
This research explored the impact of implementing Tinkercad-assisted learning media on the learning outcomes of 11th-grade Electronics Engineering students at SMK Negeri 5 Padang, focusing on embedded system programming. Employing a quasi-experimental design with a Non-equivalent Control Group Design method, the study comprised an experimental group using Tinkercad and a control group undergoing traditional direct learning. The analysis of pretest and posttest data revealed a significant difference between the two groups, with the experimental group exhibiting an 11.5% improvement in learning outcomes. The hypothesis test, employing the t-test, yielded a t-value of 2.231, surpassing the critical t-value (1.708). Consequently, the null hypothesis (H0) was rejected, and the alternative hypothesis (H1) was accepted. The study concludes that the implementation of Tinkercad-assisted learning media had a significantly positive influence on the learning outcomes of Electronics Engineering students. These findings contribute to both practical and theoretical understanding regarding the effectiveness of Tinkercad in enhancing student learning outcomes in embedded system programming. It is recommended that further emphasis be placed on integrating Tinkercad into the curriculum to enrich students’ learning experiences and elevate the overall educational quality at SMK Negeri 5 Padang.